O-008 YI The Impact of A Nurse Navigator Program on Telephone Calls and Emergency Department Utilization Among IBD Patients. (February 2017) - Kapur, Anshika; Divakaran, Sonia; Walsh, Cynthia; Nguyen, Anne; Alacantra, Chelsea; Anda, Joseph; Curry, Yankamma; Adams, Patricia; Melmed, Gil
Abstract : Background: Inflammatory bowel disease (IBD) is a chronic relapsing condition with a high burden of illness and need for urgent and healthcare services. Recent international quality measures for IBD have highlighted the need for dedicated IBD nurses, and published studies have demonstrated associations between telephone calls and urgent/emergent care utilization. At baseline, all calls routed to a nurse were staffed by general nurses involved in multiple gastroenterology sections. We evaluated the impact of the sequential introduction of 2 dedicated IBD "nurse navigators" at a tertiary IBD center on telephone call volume and other parameters. Methods: Telephone calls to our outpatient IBD center were tracked via an Automated Call Distribution (ACD) system over an 8 month period (December 2015 to July 2016). Call frequency, duration, hold time, transfers, and abandoned calls were electronically captured. Two timeperiods were assessed: (N1) 4 months after hiring of the first nurse navigator and (N2) the first 4 months after hiring of the second nurse navigator. We also tracked emergency department (ED) utilization among our ambulatory IBD patients, and assessed whether the ED visit was preceded by a phone call to the clinic within the previous 5 days. Chart review was conducted to distinguish IBD-related ED encounters from non-IBD related encounters. Comparative statistics were performed using students' t test. Results: There were 10, 441 telephone calls to the IBD center (monthly mean ± SD = 1305 ± 119 calls/mo). There were numerically more monthly calls during N1 than N2 (1367 versus 1243, P = 0.15). The average total call time decreased from N1 to N2 (151 versus 132 seconds, P = 0.02), with a concurrent increase in the proportion of calls transferred (primarily) to the nurses (29% to 34%, P = 0.07). The average time patients were put on hold decreased from N1 to N2 (39 versus 29 seconds, P = 0.01). During the study period, there were 139 IBD-related visits to our hospital's ED; only 15 visits (11%) were preceded by a phone call to the IBD center. Hospital admission from the ED occurred in 80% of those who called prior to visiting the ED, versus 75% of those who did not call. Conclusions: The incorporation of IBD-specific nurse navigators to a tertiary outpatient IBD center may be associated with an overall reduction in phone calls to the center, decreased total call time, increased number of call transfers to nurses, and shorter hold times. Efforts to increase patient telephone contacts with IBD nurse navigators prior to visiting the ED may result in more appropriate ED use, although further evaluation is needed in larger numbers of patients.